Pengembangan Sistem Informasi Penggajian Karyawan CV. Mufidah Terminal Print berbasis Web (Studi Kasus: CV. Mufidah Terminal Print) - Chairunnisa Yusuf; Denny Sagita Rusdianto; Eriq Muhammad Adams Jonemaro (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
CV. Mufidah Terminal Print is a company in Gorontalo engaged in digital printing. Payroll system applied by CV. Mufidah Terminal Print is currently still being done conventionally, so data input errors caused by human errors often occur which lead to calculation of employee salaries, besides the payroll process is considered to take a long time, starting from the process of recording attendance, overtime, leave and permits until double checking the salary calculation results. Based on the existing problems, researchers aim to build an employee payroll system that is integrated directly with the fingerprint machine, as well as assisting in the management of overtime, leave and employee permits so as to facilitate the process of calculating employee salaries. In this study the system was built with the SDLC Prototyping model with the Evolutionary Prototyping approach. Implementation of the system is done with the Codeigniter framework and uses MySQL as a database implementation. The test results on the system both in the first and second iteration show a value of 100% valid on unit testing, integration and validation. In addition, compatibility testing shows the system can run well on various browsers and devices without any critical issues, major and minor issues.